On the dual space of a weighted Bergman space on the unit ball of Cn. (1988) - Choa, J. S.; Kim, H. O.
Abstract : The weighted Bergman spaceA α p ( B n ) ( 0 < p < 1 ), of the holomorphic functions on the unit ballB n ofC n forms anF -space. We find the dual space ofA α p ( B n ) by determining its Mackey topology.